State-of-the-art investigation of wind turbine structures by considering the soil-structure interaction phenomenon - Gravett, Dewald Z.; Markou, George (My University, 2021)
Investigating the dynamic response of wind turbine structures is of significant importance when it comes to better understanding how their behaviour is affected by different design considerations and their foundation's interaction with the soil. An extensive numerical investigation is presented herein that foresees the performance of modal and pushover analysis on a wind turbine structure that has an 80 m steel tower and is founded on different clay profiles. The 3D detailed models constructed in this research work consider the effect of soil-structure interaction by discretizing the pile foundation and soil domains through 8-noded hexahedral elements, achieving maximum modelling accuracy. An investigation was also performed on the optimum pile inclination, where based on the numerical findings, the optimum inclination of the battered piles was found to be that of 10 degrees.
Keywords: Wind Turbines; Soil-Structure Interaction; Battered Piles; Pushover Analysis; Modal Analysis; Large-Scale Numerical Models